Plant polyamines in stress and development - Ruben Alcazar (Frontiers Research Topics, 2014)
Polyamines are small aliphatic polycations which have been involved in key stress and developmental processes in plants. In the recent years, compelling genetic and molecular evidences point to polyamines as essential metabolites required for resistance to drought, freezing, salinity, oxidative stress among other type of abiotic and biotic stresses. In addition to their role as stress-protective compounds, polyamines participate in key developmental processes mediated by specific signaling pathways or in cross-regulation with other plant hormones. Our Research Topic aims to integrate the multiple stress and developmental regulatory functions of polyamines in plants under a genetic, molecular and evolutionary perspective with special focus on signaling networks, mechanisms of action and metabolism regulation.